Recent archaeological research at Saruq al‐Hadid, Dubai, UAE. (May 2017) - Weeks, Lloyd; Cable, Charlotte; Franke, Kristina; Newton, Claire; Karacic, Steven; Roberts, James; Stepanov, Ivan; David‐Cuny, Hélène; Price, David; Bukhash, Rashad Mohammed; Radwan, Mansour Boraik; Zein, Hassan
Abstract : In September 2014, the University of New England (UNE), Australia, began a three‐year programme of archaeological fieldwork and post‐excavation analyses focused on the site of Saruq al‐Hadid. In this paper, we present the initial results of our current field and laboratory research particularly related to site stratigraphy and formation processes, relative and absolute chronology, and the preliminary results of various programmes of post‐excavation analyses including archaeobotanical, zooarchaeological, ceramic and archaeometallurgical studies. These studies provide new data to build into the archaeological understanding of Saruq al‐Hadid that has, to date, focused largely on intensive excavation.